Lazisnu Dan Penanggulangan COVID 19; Impelemntasi Fatwa MUI Nomor 23 Tahun 2020 Tentang Pemanfaatan Zakat Infak Shadaqah - Ismail, Habib; Rohmawati, Ari; Rakhmat, Rakhmat; Hidayati, Niswatin Nurul (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2021)
Background. The emergence of the Covid-19 pandemic and the presence of this fatwa has become a phenomenon appearing recently. If all this time research on the use of zakat in normal situations, then a research is needed to see how the realization and implementation of the fatwa of MUI regarding the use of assets during the Covid-19 pandemic. Aim. Describing of implementation of fatwa MUI Number 23 year of 2020 about utilizing of zakat, infaq and shadaqah to cope with impact of the spread Covid-19 Methods. This research was a field research with a phenomenological approach. This research was a qualitative research using descriptive analysis of the MUI Fatwa Number 23 of 2020 and its implementation in LazisNU, Metro City. Results. The result of this research was that the implementation of the MUI fatwa Number 23 of 2020 concerning the use of zakat, infaq and shadaqah was carried out using the fatwa determination methodology with various legal considerations and based on clear legal aspects. As for the Covid-19 Outbreak management implemented by LazisNU, Metro City in the first two important aspects, fatwas was implemented conceptually through several emergency response programs implemented by the Covid-19 outbreak response officer unit. Second, the fatwa was implemented constructively, where the fatwa still paid attention to the social aspects of society by sorting out two aspects, including the distribution of zakat specifically for Moeslim communities affected by Covid-19 while for the wider non-Moeslim community affected by Covid-19, it was taken from infaq, shadaqah and other donations funds.